1998
DOI: 10.1097/00004728-199803000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Ground-Glass Attenuation in Nodular Bronchioloalveolar Carcinoma: CT Patterns and Prognostic Value

Abstract: Our series demonstrates that focal BAC may progress to diffuse pulmonary involvement by bronchogenic spread. The presence of a large area of ground-glass attenuation associated with a nodular BAC might be the CT sign of an aggressive biologic behavior. In these cases there is a high likelihood for diffuse disease to develop from bronchogenic spread.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 17 publications
0
13
0
1
Order By: Relevance
“…As to histologic cell types and density distribution of the tumor, bronchioloalveolar carcinoma has been described to show ground-glass attenuation [12,13]. We noted the well-differentiated adenocarcinoma also to demonstrate ground-glass attenuation reflecting a lepidic growth pattern (type L1).…”
Section: Discussionmentioning
confidence: 68%
“…As to histologic cell types and density distribution of the tumor, bronchioloalveolar carcinoma has been described to show ground-glass attenuation [12,13]. We noted the well-differentiated adenocarcinoma also to demonstrate ground-glass attenuation reflecting a lepidic growth pattern (type L1).…”
Section: Discussionmentioning
confidence: 68%
“…This second type of growth can be found with bronchioloalveolar carcinoma, which explains the ground-glass attenuation component that is commonly found with this type of tumor. In a series of 22 patients with bronchioloalveolar carcinoma, the halo sign was identified on CT images in two patients (16). In another series, which comprised 65 patients with lung metastases from extrapulmonary adenocarcinoma, the halo sign was present in two patients.…”
Section: Discussionmentioning
confidence: 97%
“…5). Recently, a close correlation was established between CT diagnoses of ground-glass SPNs and the histological findings of adenocarcinoma: the ground-glass component in adenocarcinomas is associated with lepidic growth or mucin production [19,22], and its possible predominance over the solid component is related to prognosis. Aoki et al showed that a predominance of solid alveolare di adenocarcinoma [6,19].…”
Section: Cavitation and Ground-glass Opacitymentioning
confidence: 99%
“…5) [21]. Recentemente si è giunti a definire una stretta corrispondenza tra le diagnosi TC di NPS a vetro smerigliato ed il corrispettivo istologico di adenocarcinoma: la componente a vetro smerigliato negli adenocarcinomi è associata alla crescita lepidica o alla produzione di mucina [19,22] e la sua preponderanza o meno rispetto alla componente solida è correlata alla prognosi. Infatti, Aoki et al [23] hanno evidenziato che la maggior presenza della componente solida nel contesto di NPS ground-glass è associata ad un comportamento maggiormente invasivo (tipi C, D, E, F della classificazione Noguchi, ovvero, rispettivamente, carcinomi bronchioloalveolari con presenza di proliferazione fibroblastica, carcinomi poco differenziati, tubulari e papillari, con un pattern di crescita di tipo compressivo) [23,24].…”
Section: Cavitation and Ground-glass Opacityunclassified